The price of safety: hidden costs and unintended consequences for women in the domestic violence service system - Shoener, Sara Jane (Vanderbilt University Press, 2016)
" Specialized public resources for survivors of intimate partner violence (IPV) are increasingly common and diverse--from protection order courts and dedicated domestic violence units in police precincts to a vast network of community-based emergency shelters and counseling services. Yet little consensus exists regarding which resources actually work to reduce violence and help survivors lead the lives they would like to live. This book is an account of these resources and IPV survivors' experiences with them in three communities in the United States. Through detailed observations of services such as court procedures, public benefits processes, and community-based IPV programs as well as in-depth interviews with dozens of IPV survivors and practitioners, Shoener describes how our current institutional response to IPV is often not useful--and sometimes quite harmful--for IPV survivors with the least material, social, and cultural capital to spare. For these women, as the interviews vividly record, IPV has long-term economic and social consequences, disrupting career paths and creating social isolation. "--